2020
DOI: 10.1155/2020/4789806
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Five TrkB Gene Polymorphisms in Schizophrenia and the Interaction of Its Haplotype with rs6265 BDNF Gene Polymorphism

Abstract: Aim. The BDNF dysfunction in the schizophrenia has been soundly documented. The TrkB gene is a high-affinity receptor of the BDNF that is changed in schizophrenia and mood disorders. The study had two aims: first, to identify whether the five nucleotide polymorphisms (SNPs) in TrkB gene are associated with a diagnosis of schizophrenia; and the latter, if any association exists between the TrkB SNPs and psychopathology, suicide attempts, and family history of schizophrenia in a Caucasian population. Methods. Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 37 publications
(48 reference statements)
0
6
0
Order By: Relevance
“…Although sex as a distinguishing biological factor is crucial in genetic studies, the social construct of gender may further bring clarity, especially in the light of research highlighting more prevalent gender dysphoria in individuals with schizophrenia than in the general population ( 53 ). Sex differences were found in the risk of developing schizophrenia by Shuchanek-Raif ( 35 ). In this study, the ATAAT haplotype (built with 5 SNPs in the TrKB gene) was associated with a lower risk for schizophrenia in men.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although sex as a distinguishing biological factor is crucial in genetic studies, the social construct of gender may further bring clarity, especially in the light of research highlighting more prevalent gender dysphoria in individuals with schizophrenia than in the general population ( 53 ). Sex differences were found in the risk of developing schizophrenia by Shuchanek-Raif ( 35 ). In this study, the ATAAT haplotype (built with 5 SNPs in the TrKB gene) was associated with a lower risk for schizophrenia in men.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple genetic interactions were explored by Su ( 41 ), Morozova ( 40 ), Zzhang ( 28 ), Kim and Kim ( 25 ), Sosin ( 30 ), Pan ( 43 ), Karacetin ( 38 ), Ping ( 45 ), and Suchanek-Raif ( 35 ), revealing various associations or propensity for risk for schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, these defects may ultimately lead to neurological and psychiatric disorders. For example, in a Polish population the polymorphisms of the BDNF receptor-TrkB (NTRK2 gene): rs10868235-T (intr) and rs1387923-G (3′UTR) was found to be associated with a higher risk of schizophrenia in men; rs1387923-A (3′UTR)-with a lower risk of schizophrenia, and the polymorphism rs1565445-A (intr)-with an increased risk of suicide in schizophrenia (Suchanek-Raif et al, 2020). It is worth noting that many of the described TrkB SNPs are associated with the predisposition to suicidal activity; therefore, it is suggested that NTRK2 polymorphisms should be screened for if there was a history of suicidal ideation.…”
Section: Neurotrophins and Their Receptorsmentioning
confidence: 99%
“…However, when the rs6265 SNP of the BDNF gene was added, a specific GTAGCG haplotype was observed, which demonstrated protective effects exclusively in women. These findings were particularly significant for the paranoid subtype of schizophrenia without concomitant depressive episodes [ 106 ].…”
Section: Polymorphismmentioning
confidence: 99%